2022
DOI: 10.1002/anie.202209394
|View full text |Cite
|
Sign up to set email alerts
|

Olefin–Borane Interactions in Donor–π–Acceptor Fluorophores that Undergo Frustrated‐Lewis‐Pair‐Type Reactions

Abstract: Olefin-borane π-complexes have been postulated as intermediates for the addition of frustrated Lewis pairs (FLP) to olefins. In the present study, we have employed this weak interaction to modulate the electronic properties of boron-based π-electron materials. A series of donor-π-acceptor (D-π-A) fluorophores that contain an alkenyl-bridged diarylboryl group is synthesized. A crystallographic analysis revealed that the olefin and boron moieties are held in close proximity. Upon addition of a Lewis base to a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Furthermore, we found that all three compounds exhibit coordination to trace residual moisture in solvents upon cooling. [22] Coordination was observed even in solvents determined to be dry via Karl Fischer titration (Supporting Information Section S3D).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found that all three compounds exhibit coordination to trace residual moisture in solvents upon cooling. [22] Coordination was observed even in solvents determined to be dry via Karl Fischer titration (Supporting Information Section S3D).…”
Section: Methodsmentioning
confidence: 99%
“…The absence of TADF in 3‐ C 2 , 3‐ C s , and 4‐ C 1 is due to significantly large Δ E ST than those for 1 and 2 . Furthermore, we found that all three compounds exhibit coordination to trace residual moisture in solvents upon cooling [22] . Coordination was observed even in solvents determined to be dry via Karl Fischer titration (Supporting Information Section S3D).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, we found that all three compounds exhibit coordination to trace residual moisture in solvents upon cooling. [22] Coordination was observed even in solvents determined to be dry via Karl Fischer titration (Supporting Information Section S3D). To probe the charge transfer (CT) characteristics of the excited state, we performed additional absorption and emission measurements for 3-C 2 , 3-C s , and 4-C 1 in non-polar 2-methylpentane and more polar 2-methyltetrahydrofuran (2-MeTHF) solvents (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…2 Although borane-olefin complexes had been considered as weakly interacting van der Waals complexes, 3,4 it has recently been shown that they can affect the structure and reactivity of molecular systems having borane and olefinic moieties in close proximity. 5–8 Yamaguchi and coworkers reported a reversible FLP-type addition reaction of Lewis bases to an olefin-containing triarylborane derivative with a structure where borane and olefin moieties are close to each other. 6 Braunschweig and coworkers revealed that the boron-bridged boranorbornadiene derivatives formed in the reaction between a borole and an alkyne derivative are in equilibrium with borepins and boranorcaradienes in solution, due to intramolecular complexation between the borane moieties and the π-system.…”
mentioning
confidence: 99%
“…5–8 Yamaguchi and coworkers reported a reversible FLP-type addition reaction of Lewis bases to an olefin-containing triarylborane derivative with a structure where borane and olefin moieties are close to each other. 6 Braunschweig and coworkers revealed that the boron-bridged boranorbornadiene derivatives formed in the reaction between a borole and an alkyne derivative are in equilibrium with borepins and boranorcaradienes in solution, due to intramolecular complexation between the borane moieties and the π-system. 7 There is growing understanding of interactions between borane and unsaturated C–C bonds in terms of their chemical reactivities.…”
mentioning
confidence: 99%